Increasing Cumulative Impacts of Droughts Under Climate Change Does Not Alter the Ecosystem Resilience in India - Vijaykumar Bejagam; Ashutosh Sharma (Earth's Future, 2025)
Abstract Drought significantly impacts plant carbon uptake, a critical process for regulating atmospheric CO2. With the intensification of droughts under climate change, understanding ecosystem responses to these events is essential. In this study, we analyzed the impacts of droughts on Net Primary Productivity (NPP) in India over the 21st century. We tested two hypotheses: (a) increasing drought intensity and frequency will exacerbate NPP reductions, and (b) climate warming will diminish ecosystem resilience, leading to greater NPP reductions per drought event. To evaluate ecosystem responses, we employed a Multi‐Dimensional Resilience Index (MDRI), which integrates resistance and recovery time to quantify resilience. Our analysis revealed a substantial increase in extreme and moderate droughts, while mild droughts remained stable. Extreme droughts were projected to cause NPP reductions three times greater under the SSP2‐4.5 scenario and six times greater under the SSP5‐8.5 scenario compared to the baseline period (1850–2014). Ecosystems in the Western Ghats and lower Himalayan regions demonstrated moderate resilience due to prolonged recovery times and moderate resistance. Conversely, ecosystems in Northeastern India exhibited high resilience, characterized by strong resistance and shorter recovery periods. Interestingly, while resistance exhibited an increasing trend, likely influenced by carbon fertilization, recovery times showed a declining trend, potentially linked to rising temperatures. These findings do not support the second hypothesis, as no significant changes in overall ecosystem resilience were observed due to compensatory effects between resistance and recovery. This study can inform conservation strategies aimed at mitigating the adverse impacts of drought on carbon cycling.